2012
DOI: 10.1007/s00276-012-0976-1
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between left ventricular 17 myocardial segments and coronary anatomy obtained by multi-detector computed tomography: an ex vivo contribution

Abstract: In our experiment, LAD territory was larger than the AHA-proposed 17-segment model. The most specific segments were located at the anterior wall and supplied exclusively by LAD. No specific segment could be exclusively attributed to RCA or to LCx. Sometimes, LCx can be the most important artery for the blood supply of the inferior wall even if the origin of the posterior descending artery is the RCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…Considering the report by Donato et al [2], which emphasized an exclusive predominance (>95 %) by LAD in basal segments of anterior and anteroseptal wall, the normal perfusion in basal segments in the pLAD group might have been resulted from preserved perfusion from left main branch. The perfusion defect in the lateral portion of basal anterior segment in a patient with mid-LAD stenosis can be associated with combined stenosis of the first diagonal branch ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Considering the report by Donato et al [2], which emphasized an exclusive predominance (>95 %) by LAD in basal segments of anterior and anteroseptal wall, the normal perfusion in basal segments in the pLAD group might have been resulted from preserved perfusion from left main branch. The perfusion defect in the lateral portion of basal anterior segment in a patient with mid-LAD stenosis can be associated with combined stenosis of the first diagonal branch ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Our data from multi-vessel disease patients were directly compared with other studies derived from subjects with single-vessel diseases. But we chose the LAD territory because it was demonstrated to be LAD-dominant in several studies [2,26]. Hemodynamic change can still be a problem because multi-vessel disease induces coronary steal phenomenon via collateral circulation [27], which was not definitely observed in our patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the AHA noted that the name of the segments should define the location relative to the long axis of the heart and the circumferential location, and individual myocardial segments can be assigned to the three major coronaries by considering their anatomic variabilities (2) . In addition, contrary to the conventional 17‐segment model, several studies have reported, using single‐photon emission computed tomography (SPECT), cardiac magnetic resonance (CMR), and CT, that there are variations in the mapping of segments to left ventricular territories, due to their anatomic variations 3 , 4 , 5 . Therefore, they proposed a revised mapping of segments considering anatomic variations, where some segments were assigned to multiple territories due to per‐patient variability.…”
Section: Introductionmentioning
confidence: 99%